Strategies for Managing Accounts Receivable and Payable in Micro and Small Enterprises in Sidenreng Rappang Regency: The Phenomenon of Credit Practices in Grocery Store - Salam, Mifta Farid; Suriadi, Suriadi; Salida, Amrizal; Yahya, Yahya (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The growing number of customers who purchase goods on credit has become a serious threat to the sustainability of small grocery stores. The issue becomes even more complex when those customers are friends, relatives, or neighbors, making store owners feel reluctant to collect debts. Therefore, this study seeks to analyze this phenomenon in depth and develop strategies for business owners to address the problem. This research employs a descriptive qualitative and phenomenological approach, with data analysis techniques referring to the Miles and Huberman model, which consists of three stages: data reduction, data display, and conclusion drawing/verification. To ensure the validity of the data, triangulation was conducted by comparing information from multiple informants, comparing data collected at different times, and cross-checking data from observations, documentation, and interviews. Informants were selected using nonprobability sampling with a purposive sampling approach. Data collection techniques included semi-structured interviews, observations, and documentation. The findings indicate that the credit phenomenon in grocery stores is a multidimensional issue involving not only economic aspects but also deeply intertwined with social norms, moral values, and the community's social capital. The primary factors causing store owners to hesitate in collecting debts include sincerity, expectations that customers will pay on their own, feelings of reluctance, sympathy, fear of damaging social relationships, and trust in customers. Business owners generally respond to consumer credit behavior in three ways: firmly refusing to give credit, granting credit with specific conditions, or regularly collecting payments. On the other hand, business losses are also influenced by irresponsible customer behavior, such as fraud, theft, dishonesty, lack of accountability, and cases where customers experiencing personal difficulties choose to disappear. To maintain business continuity, effective strategies include preventive (prevention), curative (resolution), and adaptive (sustainability) approaches, all grounded in strong social capital—trust, communication, and social solidarity.